Potensi Wortel (Daucus Carota) Sediaan Mentah dan Matang terhadap Penurunan Kadar Kolesterol Tikus Putih (Rattus Norvegicus) - Erni Setiyorini (Journal of Ners and Midwifery, 2014)
Asthma bronchiale that occurs in children will have an impact on daily activities. Based on the registers data of childhood asthma in children clinic Mardi Waluyo BlitarHospital January - June 2012 amounted to 114 children , with 57 new cases of asthma children and 57 children an old case that repeated treatment. This suggests that the asthma control level inÂ  partially controlled and uncontrolled . The purpose of this study was to analyze relationship between environmental factors with the asthma control level children who went to Pediatric Clinic Mardi Waluyo Blitar Hospital.Method: Research design was cross-sectional , using purposive sampling techniques obtained a sample of 32 respondents. Data collection was conducted in October 2012 using a questionnaire Childhood Asthma Control Test ( C - ACT ) . Descriptive data analysis and statistical analysis using the Spearman Rank test . The results showed that Spearman Rho test with p-value= 0.025 , which means there is a relationship between environmental factors with the level of control of childhood asthma. Discussion:Environmental factors stay near the farm, the family members who smoke , have pets is a precipitating factor of asthma . Exposure to environmental factors can cause a level of uncontrolled asthma. It is expected that health workers can provide education to families and patients on the control of environmental factors to improve the level of asthma control.